Development of methodology for efficiency evaluation of cluster interaction of industrial enterprise - Lesko, Alexandr; Ratushnnyak, Olga; Glushchenko, Larysa (Technology audit and production reserves, 2017)
The object of research is efficiency evaluation of the cluster interaction. World experience convinces that cluster interaction significantly reduces the amount of costs and efforts for competitive rivalry and allows combining the advantages of enterprises. For efficient industrial enterprise business activity within the cluster it is necessary to develop and apply modern methods of efficiency evaluation of a cluster interaction at the level of an industrial enterprise. The lack of a scientifically based methodology for a comprehensive efficiency evaluation of the cluster interaction of an industrial enterprise does not allow an enterprise to determine the most promising areas of such interaction with cluster participants. An analysis of existing methodological approaches has shown that most scientists propose an evaluation either on a cluster scale or at a regional level. Effectiveness evaluation of the cluster cooperation on enterprise-participant of the cluster paid insufficient attention level. In addition, traditional methods of multifactor analysis of complex economic systems do not allow describing the cause-effect relationship between the parameters of impact and the predicted value using factors that take into account qualitative indicators. Therefore, to evaluate the cluster interaction, the authors proposed to use fuzzy set theory, which allows to make optimal management decisions taking into account the quantitative and qualitative parameters. As a result of the research, a comprehensive methodology is developed that takes into account the basic directions of cluster interaction based on quantitative and qualitative indicators of production, technology, innovation, financial and economic, personnel, information, marketing and management interactions based on fuzzy set theory, which will allow making optimal management decisions about effectiveness of cluster interaction of industrial enterprise as a complex and separately for its directions. The theoretical value of the research is to develop a methodology and tool to ensure the effective functioning of the processes of the industrial enterprise in the cluster. The practical significance of obtained results is that they can be used by specific industrial enterprises when choosing the forms and directions of cluster interaction.